Regulatory T cells trigger effector T cell DNA damage and senescence caused by metabolic competition - Liu, Xia (Nat Commun, 2018)
Defining the suppressive mechanisms used by regulatory T (Treg) cells is critical for the development of effective strategies for treating tumors and chronic infections. The molecular processes that occur in responder T cells that are suppressed by Treg cells are unclear. Here we show that human Treg cells initiate DNA damage in effector T cells caused by metabolic competition during cross-talk, resulting in senescence and functional changes that are molecularly distinct from anergy and exhaustion. ERK1/2 and p38 signaling cooperate with STAT1 and STAT3 to control Treg-induced effector T-cell senescence. Human Treg-induced T-cell senescence can be prevented via inhibition of the DNA damage response and/or STAT signaling in T-cell adoptive transfer mouse models. These studies identify molecular mechanisms of human Treg cell suppression and indicate that targeting Treg-induced T-cell senescence is a checkpoint for immunotherapy against cancer and other diseases associated with Treg cells.